Challenges and opportunities for scaling up infection prevention and control programmes in rural district hospitals of Tamil Nadu, India - Guhan, Maya; Kumar, Mohan; Butzin-Dozier, Zachary; Graham, Jay (International Journal of Infection Control, 2021)
Introduction: The aim of this study was to explore the barriers to implementing an infection prevention and control (IPC) programme in three public district hospitals in Tamil Nadu by interviewing key stakeholders involved in the roll-out of the programme. Materials and methods: Investigators conducted interviews (n = 17) with chief medical officers (CMOs), physicians, and IPC nurses at three secondary public district hospitals and their affiliated primary health centres (PHCs). Results: Six major themes emerged from the interviews: (1) prevalent IPC practices before the programme began; (2) barriers to implementation; (3) perceptions of the effectiveness of the IPC programme; (4) suggestions for future expansion of the programme; (5) the role of healthcare sanitation workers, and (6) water, sanitation and hygiene (WaSH) infrastructure. Stakeholders noted improvements in IPC knowledge, infection control related behaviour, and overall healthcare quality in the three hospitals. In regards to the future of this programme, stakeholders noted the need for more institutional support, a staff nurse solely dedicated to IPC, and the continued training of all staff members. Discussion: The results of this study highlight the importance of having high-functioning WaSH infrastructure and training for hospital sanitary workers in order to have an effective IPC programme. While the scale-up of this IPC programme is warranted, the barriers to implementation outlined in this study should be considered. To achieve a more effective IPC programme, we suggest that the following steps be carried out: (1) dedicate at least one full-time nurse to implementing IPC activities at each district hospital; (2) ensure that state and national policies for IPC are synchronised, and (3) provide sufficient and consistent funding for IPC activities.